Nature and Effectiveness of Rehabilitation Programmes in Preventing Inmates’ Recidivism in Nigeria Correctional Service - Omoruyi, Osagie Lucky; Agbontaen, Emike Selina Igbafe (NIU Journal of Social Sciences; Vol 10 No 2 (2024): NIU Journal of Social Sciences, Vol. 10 No. 2, June 2024, 2024)
This study examined the nature and effectiveness of rehabilitation programmes in preventing inmates’ recidivism in Nigeria Correctional Service. The rehabilitative theory was adopted as the study’s theoretical framework. The study was purely quantitative and the cross sectional research design regulated the research methodology. The collection of quantitative data involved the participation of 695 respondents to whom questionnaire was administered. The quantitative data was analysed with Statistical Package for Social Sciences (SPSS) using frequency, tables and charts. The study found out that there were different types of rehabilitation programmes in the custodial centres. These different types of rehabilitation programmes were to meet the different rehabilitation needs of the convicts. On the effectiveness of the various rehabilitation programmes, majority of the respondents in entire sampled population unanimously agreed that the rehabilitation programmes available in the custodial centres has effectively change the lives of convicts. The study concluded that effective rehabilitation of convicts can prevent inmates from going to crime and government should always prepare a discharge package for convicts upon completion of sentence, in a way that the gains of convicts’ rehabilitation will be far more than the gains of crime. The study further recommended that modern rehabilitation programmes such as prison work programmes among others should be institutionalized in custodial centres in Nigeria. Keywords: Effectiveness, Rehabilitation Programmes, Convicts, Recidivism, Custodial Centre